Procesos organizacionales del Cuerpo de Bombero Municipal de la Ciudad de Babahoyo - Murillo Sánchez, Janny Guissela (2020)
For the mentioned investigative work, the current condition of the worthy Babahoyo’s Municipal Fire Department is considered, which is a public law institution that provides fire prevention services, relief and provides various support in risk prevention programs to public and private entities, The purpose of this research case is to analyze the influence of organizational processes on job performance through an internal evaluation of the company discussed above, therefore, it is essential to point out, based on the different theoretical supports of a series of authors, methods of research and tools such as the interview and the survey, is possible to obtain valid results that diagnose that it is evident that the organizational processes influence the development of the administrative functions of collaborators to the point that a wrong perception of the institution begins to form due to the dissatisfaction of its employees, due to the fact that superior managers do not exercise exemplary leadership that projects inspiration and motivation to their work team at the time of decision-making to resolve disagreements between employees through assertive communication and teach them to accept continuous improvement challenges.